Let the drawing do the telling - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Comics with an Attitude A Guide to the Use of Comics in Development Information. L Packalén and F Odoi. Ministry of Foreign Affairs of Finland, Department for International Development Cooperation. 1999. 96 pp. ISBN 951 724 271 9 Available free